Estimation of parameters for the stochastic linear delay growth law through the L1 distance procedure - Rupšys, Petras (Lietuvos matematikos rinkinys, 2023)
This paper considered deterministic and stochastic delayed linear growth laws for the modeling of the process of growth.  For the estimation of parameters the L1 distance procedure was proposed. As an illustrative experience was used a real data set from repeated measurements on permanent sample plots of pine stands in Lithuania.
Keywords: stochastic delay differential equation; Fokker–Planck equation; stationary density; L1 distance